New Tools to Identify the Location of Seagrass Meadows: Marine Grazers as Habitat Indicators - Hays, Graeme C.; Alcoverro, Teresa; Christianen, Marjolijn J. A.; Duarte, Carlos M.; Hamann, Mark; Macreadie, Peter I.; Marsh, Helene D.; Rasheed, Michael A.; Thums, Michele; Unsworth, Richard K. F.; York, Paul H.; Esteban, Nicole (Frontiers in Marine Science, 2018)
Seagrasses are hugely valuable to human life, but the global extent of seagrass meadows remains unclear. As evidence of their value, a United Nations program exists (http://data.unep-wcmc.org/datasets/7) to try and assess their distribution and there has been a call from 122 scientists across 28 countries for more work to manage, protect and monitor seagrass meadows (http://www.bbc.com/news/science-environment-37606827). Emerging from the 12th International Seagrass Biology Workshop, held in October 2016 has been the view that grazing marine megafauna may play a useful role in helping to identify previously unknown seagrass habitats. Here we describe this concept, showing how detailed information on the distribution of both dugongs (Dugong dugon) and green sea turtles (Chelonia mydas) obtained, for example, by aerial surveys and satellite tracking, can reveal new information on the location of seagrass meadows. We show examples of how marine megaherbivores have been effective habitat indicators, revealing major, new, deep-water seagrass meadows and offering the potential for more informed estimates of seagrass extent in tropical and sub-tropical regions where current information is often lacking.